Analisis Semiotika pada Film Dua Hati Biru Semiotics Analysis On The Film “Dua Hati Biru” - Lathif, Zulfaqqar Fadhil Atha; Hakim, Lukman (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2025)
This study investigates the issue of teenage marriage in the film Dua Hati Biru, focusing on women's perspectives on teenage marriage and how women take a central role. This study aims to analyze the application of semiotic theory in the film Dua Hati Biru and explore the moral messages contained therein. By using a qualitative approach. Data collection techniques are carried out through observation, documentation, and literature studies. Meanwhile, data analysis follows the steps of sign identification, denotative, connotative, and myth analysis to gain a deeper understanding. The results of the study show that the denotative meaning in this film reflects Dara and Bima's efforts to build a harmonious family after getting pregnant out of wedlock, while the connotative meaning highlights the social stigma against young marriage. Meanwhile, the social myth in this film is related to young marriage, premarital pregnancy, and the role of parents. Society often gives a negative stigma to marriage at a young age, which creates social pressure for Bima and Dara. In addition, the myth about gender roles shows injustice, where women are considered fully responsible for raising children, while men are expected to be breadwinners. This film also highlights the role of the family as a source of support as well as conflict, where the hopes and expectations of the family can burden individuals. Behind their love story, this film implies hope and struggle to find happiness despite facing many challenges. Recommendations for further research are the need to analyze the psychological impact experienced by female characters and how these representations influence society's views on young marriage.